Analysis of the Decadal Kinematic Characteristics of the Daguangbao Landslide Using Multiplatform Time Series InSAR Observations After the Wenchuan Earthquake. Issue 12 (2nd December 2020) - Luo, Xingjun; Wang, Changcheng; Long, Yan; Yi, Zhonghai
Abstract: The Daguangbao landslide was the largest landslide triggered by the "5.12" Wenchuan Mw 7.9 earthquake. This landslide is among the few superlarge‐scale landslides of 1 billion m 3 magnitude worldwide. As the landslide accumulation represents a potential hazard, long‐term monitoring and geological interpretation of the Daguangbao landslide is important to reveal the postsliding deformation characteristics and laws of this landslide type. To study the kinematic characteristics 10 years postearthquake, the landslide accumulation deformation was monitored in two stages using different data sets and processing methods. First, regarding the deformation 2 years postearthquake, we selected PALSAR‐1 data (21 October 2008 to 14 March 2011) and obtained the LOS (line of sight) direction time series deformation of the landslide using the Small BAseline Subset (SBAS) algorithm. Second, for the last 4.5 years of deformation, Sentinel‐1 data sets (26 November 2015 to 8 June 2020) in two ascending and one descending path are experimentally used. The vertical and east‐west deformations during this period are obtained. Thickness, topography, precipitation, and other factors are combined to analyze the landslide accumulation deformation. The landslide accumulation volume decreases under gravitational influence, shrinkage is accelerated under precipitation influence, and periodic fluctuations occur, which lag precipitation changes. The maximum vertical direction deformation rate is below 80 mm/year, and the deformation magnitude in the east‐west direction is approximately ±35 mm/year. Local deformation is still affected by the surface slope and aspect, and the overall landslide accumulation movement trend involves gathering of the eastern and western parts toward the middle. In the observation window, with the stabilization of accumulation, the deformation tends decrease. Key Points: Analysis of the decadal kinematic characteristics of the landslide shows that landslide deformation tends to be decreasing The overall landslide accumulation movement trend involves gathering of the eastern and western parts toward the middle The landslide accumulation volume decreases under gravitational influence, and shrinkage is accelerated under precipitation influence